2011
DOI: 10.1103/physrevc.83.024907
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus-nucleus interaction between boosted nuclei

Abstract: The nucleus-nucleus interaction potential has been studied within the relativistic mean field theory. The systematics of the relativistic effects have been investigated by analyzing the relation between the potential and the bombarding energy as a function of the impact parameter. It is shown that the potential barriers are noticeably sensitive to the bombarding energy for a given impact parameter. At large bombarding energies the slope at the potential edge decreases with the impact parameter. Comparisons wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A proper relativistic treatment of nuclear potentials in breakup reactions at intermediate energies (E lab > 30 MeV/nucleon) requires the use of an effective mesonexchange theory combined with proper Lorentz transformations, as shown by Long and Bertulani (2011). This theory leads to appreciable deviations from the standard optical model method widely used in low-energy reactions.…”
Section: Coulomb Dissociationmentioning
confidence: 99%
“…A proper relativistic treatment of nuclear potentials in breakup reactions at intermediate energies (E lab > 30 MeV/nucleon) requires the use of an effective mesonexchange theory combined with proper Lorentz transformations, as shown by Long and Bertulani (2011). This theory leads to appreciable deviations from the standard optical model method widely used in low-energy reactions.…”
Section: Coulomb Dissociationmentioning
confidence: 99%
“…The relativistic treatment is adopted in all the reaction kinematics in this calculation as well as the kinematics of the p-α binary collision. Recently, the importance of the dynamical relativistic corrections to the Coulomb and nuclear interactions has been revealed for the breakup reactions [53][54][55][56]. To see the effect of the dynamical relativistic corrections in the (p, pα) knockout reactions will be interesting, but it is beyond the scope of current study.…”
Section: A Numerical Inputsmentioning
confidence: 97%
“…We have shown here an example, based on the relativistic mean field theory [57]. The relativistic effects have been studied by analyzing the dependence of the potentials upon bombarding energies and impact parameters.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure has shown that relativistic corrections lead to appreciable changes of inelastic processes involving 100 MeV/nucleon projectiles. A microscopic theory to describe the covariant properties of the nuclear potential was later developed [57]. We briefly describe its main results.…”
Section: The Nucleus-nucleus Interaction Between Boosted Nucleimentioning
confidence: 99%